1991
DOI: 10.1109/55.79563
|View full text |Cite
|
Sign up to set email alerts
|

Physical understanding and optimum design of high-power millimeter-wave pulsed IMPATT diodes

Abstract: The purpose of this paper is a physical understanding of the specifw mode of operation of high-power millimeterwave pulsed IMPA'IT diodes, derived from a self-consistent numerical model. The theoretical results fit well with recently published experimental findings, and thus allow an optimum design of the 94-GHz IMPATT structure for peak output power in excess of 50 W under low duty cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…On the theoretical side, several investigators have published explanations for high power generation from silicon [5][6][7] and GaAs [8] flat DDR IMPATTs at mm-wave frequencies. Of these, Dalle et al [5], Rolland et al [6] and Gaul and Classen [8] suggested that the phenomenon of high power generation was due to pin mode operation of the devices at high current densities. Chen et al [7], on the other hand, suggested that the high power generation might be due to TRAPATT mode operation of silicon DDRs.…”
Section: Introductionmentioning
confidence: 99%
“…On the theoretical side, several investigators have published explanations for high power generation from silicon [5][6][7] and GaAs [8] flat DDR IMPATTs at mm-wave frequencies. Of these, Dalle et al [5], Rolland et al [6] and Gaul and Classen [8] suggested that the phenomenon of high power generation was due to pin mode operation of the devices at high current densities. Chen et al [7], on the other hand, suggested that the high power generation might be due to TRAPATT mode operation of silicon DDRs.…”
Section: Introductionmentioning
confidence: 99%
“…We have also computed the expected rf output power and dc-to-rf conversion efficiency from each of the IMPATT diode structures according to equations ( 6) and (7). The related values at the designed frequency of 220 GHz are listed in table 3.…”
Section: Resultsmentioning
confidence: 99%
“…5.41×10 6 1.34×10 8 5.41×10 6 b p (V cm −1 ) 1.96×10 7 2.03×10 7 3.92×10 7 cross-area of the diode, V dc and I dc are the dc voltage and current, respectively.…”
Section: Materials Parameters and Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation